SERVBID: the development of a B2C service brand identity scale. Issue 5 (20th April 2020) - Pareek, Vandana; Harrison, Tina
Abstract : Purpose: This paper re-conceptualizes and measures brand identity (BI) from a services perspective. This paper aims to develop and test a psychometrically valid and reliable scale to measure service brand identity (SERVBID). Design/methodology/approach: A multi-stage research design was adopted drawing on qualitative and quantitative studies consistent with extant scale development procedures. Qualitative studies comprised a comprehensive literature review, expert panel review and interviews to develop a theoretical framework and generate items. Quantitative studies comprised pilot testing ( n = 106), online survey for scale development ( n = 246) and scale validation ( n = 245) on UK-based consumers using exploratory and confirmatory factor analysis. Findings: The study finds support for a five-dimensional SERVBID scale comprising: process identity; organization identity; symbolic identity; servicescape identity; and communication identity. Practical implications: The SERVBID scale provides practitioners with a practical tool to understand, benchmark and assess SERVBID. The scale will assist marketers in assessing the strength of BI overall as well as the strength of individual facets of BI. Originality/value: This study provides a deeper and complete understanding of the theoretical construct of BI through a service-dominant lens, in particular recognizing the defining role of the service process and servicescape in SERVBID construction.